A Brucella spp. Isolate from a Pac-Man Frog (Ceratophrys ornata) Reveals Characteristics Departing from Classical Brucellae - Soler-Lloréns, Pedro F.; Quance, Chris R.; Lawhon, Sara D.; Stuber, Tod P.; Edwards, John F.; Ficht, Thomas A.; Robbe-Austerman, Suelee; O'Callaghan, David; Keriel, Anne (Frontiers in Cellular and Infection Microbiology, 2016)
Brucella are highly infectious bacterial pathogens responsible for brucellosis, a frequent worldwide zoonosis. The Brucella genus has recently expanded from 6 to 11 species, all of which were associated with mammals; The natural host range recently expanded to amphibians after some reports of atypical strains from frogs. Here we describe the first in depth phenotypic and genetic characterization of a Brucella strains isolated from a frog. Strain B13-0095 was isolated from a Pac-Man frog (Ceratophyrus ornate) at a veterinary hospital in Texas and was initially misidentified as Ochrobactrum anthropi. We found that B13-0095 belongs to a group of early-diverging brucellae that includes Brucella inopinata strain BO1 and the B. inopinata-like strain BO2, with traits that depart significantly from those of the ‘classical’ Brucella spp. Analysis of B13-0095 genome sequence revealed several specific features that suggest that this isolate represents an intermediate between a soil associated ancestor and the host adapted ‘classical’ species. Like strain BO2, B13-0095 does not possess the genes required to produce the perosamine based LPS found in classical Brucella, but has a set of genes that could encode a rhamnose based O-antigen. Despite this, B13-0095 has a very fast intracellular replication rate in both epithelial cells and macrophages. Finally, another major finding in this study is the bacterial motility observed for strains B13-0095, BO1 and BO2, which is remarkable for this bacterial genus. This study thus highlights several novel characteristics in strains belonging to an emerging group within the Brucella genus. Accurate identification tools for such atypical Brucella isolates and careful evaluation of their zoonotic potential, are urgently required.